Multiple point competition - Karnani, Aneel; Wernerfelt, Birger (Strategic Management Journal, 1985)
Situations where firms compete against each other simultaneously in several markets abound in real life. However, there is very little conceptual or theoretical literature on multiple point competition. This paper offers a first attempt at developing a conceptual framework for analysing and understanding situations involving multiple point competition. Several examples are discussed to provide insights into the options available to the competitors and the equilibrium outcomes of such competition.